Towards More Effective Public Services: E-readiness Analysis of Indonesia’s BNN One Stop Service (BOSS) - P.Wiryawan Paritranaya; Ida Ayu Oka Martini (Magister Ilmu Administrasi Publik, 2025)
This study investigates the e-readiness of Indonesia's BNN One Stop Service (BOSS), a digital initiative aimed at enhancing drug abuse prevention and recovery services. With a focus on the Bali Province, selected for its high City Drug Threat Response (KOTAN) index, the research examines the challenges BOSS faces in a region struggling with significant drug-related issues. This case study offers valuable insights into the barriers hindering the effective delivery of digital public services in resource-constrained areas. Using the modified STOPE Framework (Strategy, Technology, Organization, People, Environment, and the newly introduced Budgeting domain), the study assesses the operational readiness of BOSS. The methodology includes 13 in-depth interviews with key respondents, including supervisory leaders, service staff, and BOSS operators. The research identifies several operational challenges, including outdated ICT infrastructure, slow internet speeds, and a lack of coordination with other government agencies, that impede service efficiency. Additionally, it reveals significant gaps in the budgeting process, where centralized procurement and financial constraints have caused delays in acquiring critical technology and resources. This study contributes to the field of e-government readiness by introducing the Budgeting domain into the STOPE Framework, thus expanding the scope of e-readiness assessments. The findings highlight the complex interplay between leadership, infrastructure, and regulatory frameworks, providing valuable insights into the challenges of successful digital service delivery, especially in resource-limited settings.